2014
DOI: 10.1186/1475-2840-13-10
|View full text |Cite
|
Sign up to set email alerts
|

Leptin is associated with vascular endothelial function in overweight patients with type 2 diabetes

Abstract: BackgroundThe adipocyte-derived hormone leptin plays a key role in the regulation of appetite and body weight. Recent studies have suggested that leptin is also involved in the pathogenesis of obesity-related atherosclerosis and cardiovascular disease. In this study, we investigated the association of plasma leptin levels with vascular endothelial function in lean and overweight patients with type 2 diabetes.MethodsOne hundred seventy-one type 2 diabetic patients, of which 85 were overweight (body mass index (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 47 publications
2
41
0
2
Order By: Relevance
“…Obesity is an important contributor to the development of Type 2 diabetes and cardiovascular diseases (2,15,17,44). Impairments in vascular function associated with obesity are attributable to concomitant systemic risk factors including hypertension, hyperlipidemia, hyperglycemia, hyperinsulinemia, inflammatory cytokines, and sympathetic overactivity (5,20,25,27,40,41). Notably, there is evidence that obesityrelated endothelial dysfunction and structural changes are not homogenous throughout the arterial tree.…”
mentioning
confidence: 99%
“…Obesity is an important contributor to the development of Type 2 diabetes and cardiovascular diseases (2,15,17,44). Impairments in vascular function associated with obesity are attributable to concomitant systemic risk factors including hypertension, hyperlipidemia, hyperglycemia, hyperinsulinemia, inflammatory cytokines, and sympathetic overactivity (5,20,25,27,40,41). Notably, there is evidence that obesityrelated endothelial dysfunction and structural changes are not homogenous throughout the arterial tree.…”
mentioning
confidence: 99%
“…On the other hand, it is also reported that plasma adipocytokine levels such as leptin were positively associated with vascular endothelial function in overweight patients (Morioka et al 2014). Therefore, adipose tissue may have some influence on endothelial function.…”
Section: Limitations Of This Studymentioning
confidence: 93%
“…WC was measured to the nearest centimeter at the level of the umbilicus in a standing position at the end of gentle expiration. Blood was drawn after an overnight fast, and biochemical parameters were analyzed by a standard laboratory method as previously described 26) .…”
Section: Methodsmentioning
confidence: 99%